Human dependence on nitrogen fertilizers and its consequences - De la Torre, Fernando; Cañas, Rafael A (Encuentros en la Biología, 2014)
In the current demographic context, with a excessive population growth worldwide and a continuous increase in the level oflife in especially populated countries, cover the nutritional needs and demands of humanity has become an extraordinary challenge.